Preliminary studies of neurosensory and cardiopulmonary health compromise in captive- bred Rhesus macaques (Macaca mulatta) suffering scoliosis - Hernández-Godínez, Braulio; Ibáñez-Contreras, Alejandra; Reyes-Pantoja, Sergio; Durand-Rivera, Alfredo; Galvan-Montaño, Alfonso; Perdigón-Castañeda, Gerardo; Carmen Climent-Palmer, Ma; Tena-Betancourt, Eduardo (Journal of medical primatology, 2012)
Background  It has been widely documented that quadrupedal animals rarely display natural spontaneous scoliotic rachis deviations of the spinal column. The objective was to determine spinal deformities developed by geriatric monkeys of the Macaca mulatta species, by radiographical and tomographical studies of the vertebral column correlating morphological changes with altered physiological parameters and electrical neurosensorial conductivity of somatosensory‐evoked potentials (SEPs). Materials and methods  A cohort of six geriatric monkeys was used: three non‐scoliotic subjects and three monkeys with naturally acquired true scoliosis. Results  Radiographic and tomographic studies depicted a thoracic curvature displaying a left‐sided thoracic vertebral rotation. The evaluation of physiological parameters demonstrated significant differences in the respiratory rate, as it was observed for the diastolic blood pressures, which showed a decrease in the monkeys with scoliosis compared with healthy monkeys. Regarding the SEPs studies, the non‐parametric test for independent samples Mann–Whitney U test displayed a significant difference observed at the left and right thoracic derivative in P1; while regarding the study of upper limbs, a significant difference was seen at the Erb’s point derivative, left afferency in P1, showing in all the derivatives an increase in latency in monkeys with scoliosis versus monkeys in the control group. Conclusions  This study has demonstrated that quadrupedal animals can develop true scoliosis showing an analogous way to that occurring in humans.